A HOMOGENEOUS EARTHQUAKE CATALOG OF INTERMEDIATE-DEEP FOCUS GLOBAL SEISMICITY: COMPLETENESS AND SPATIO-TEMPORAL ANALYSIS - Tsampas, A.D.; Scordilis, E.M.; Papazachos, C.B.; Karakaisis, G.F. (Bulletin of the Geological Society of Greece, 2016)
homogeneous with respect to magnitude earthquake catalog is compiled, particularly focusing on the global intermediate depth-deep focus seismicity and by exploiting data of almost half-century. Within a two-step compilation process, we take advantage of 10 robust conversion equations produced exclusively for intermediate depth and deep focal data (Tsampas et al., 2016). Initially, magnitudes of different scales and several origins are converted into proxy moment magnitudes (Mw* Mw) and a weighted mean-value aggregation procedure is then applied for all events with estimated Mw*. Therefore, a homogeneous magnitude scale (equivalent to Mw) is obtained as result of individual correlations between different magnitude scales and the moment magnitude (Mw) scale, yielding a unique magnitude value per event. Moreover, through implementing a simple optimization scheme, a composed, unique depth value per event is estimated, utilizing focal data from multiple resources. In the end and after validating magnitude’s (M) reliability, a brief spatiotemporal analysis of the provided catalog is performed, revealing its potential for further exploitation in large scale seismological surveys or other research studies of global interest.